PERANAN PERBANKAN SYARIAH TERHADAP PENGEMBANGAN BAITUL MAL WAT TAMWIL (BMT) DI KOTA MEDAN - Danu Ramadhan; Haroni Doli H. Ritonga (Departemen Ekonomi Pembangunan USU, 2012)
This study aims to determine how large the influence of Islamic Bank system on the development of BMT in Medan and the problem that facing BMT which made them hard to develop. The method used in this study is descriptive method of analysis by the method of collecting data and explain it with words that occur in accordance with the field, resulting in the conclusion. Techniques of data collection by distributing questionnaires in five BMT Medan city with a population of 50 BMT. From the analysis it can be concluded that the most of Islamic Bank a place to save money, especially in the form of savings mudharabah and wadi'ah greater than finance especially in Mudharabah, Musyarakah and services of Islamic Financial Institution. The next results of problem the internal BMT in the city of Medan is capital, product and the non perfoming loan and then the external problem is the existence of loan sharks are cause slow growing of BMT.